2001
DOI: 10.1182/blood.v97.5.1491
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 increases both thymic-dependent and thymic-independent T-cell regeneration after bone marrow transplantation

Abstract: Thymic-dependent differentiation of bone marrow (BM)-derived progenitors and thymic-independent antigen-driven peripheral expansion of mature T cells represent the 2 primary pathways for T-cell regeneration. These pathways are interregulated such that peripheral T-cell expansion is increased in thymectomized versus thymus-bearing hosts after bone marrow transplantation (BMT). This study shows that this interregulation is due to competition between progeny of these 2 pathways because depletion of thymic progeny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
190
5
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(204 citation statements)
references
References 42 publications
7
190
5
2
Order By: Relevance
“…Because peripheral human T cell analysis is not easily conducted in SCID-hu Thy/Liv mice (64), we did not measure TCR rearrangement and cannot exclude the possibility that IL-7 enhances TCR rearrangement excision circles formation in this model. Finally, our data are not consistent with evidence that exogenous IL-7 enhances thymopoiesis in mice after bone marrow transplantation (65,66). It has been demonstrated that the effects of IL-7 in this setting are attributable to radiation-induced damage to IL-7-producing thymic stromal cells resulting in decreased endogenous IL-7 production in transplanted mice (67).…”
Section: Discussioncontrasting
confidence: 56%
“…Because peripheral human T cell analysis is not easily conducted in SCID-hu Thy/Liv mice (64), we did not measure TCR rearrangement and cannot exclude the possibility that IL-7 enhances TCR rearrangement excision circles formation in this model. Finally, our data are not consistent with evidence that exogenous IL-7 enhances thymopoiesis in mice after bone marrow transplantation (65,66). It has been demonstrated that the effects of IL-7 in this setting are attributable to radiation-induced damage to IL-7-producing thymic stromal cells resulting in decreased endogenous IL-7 production in transplanted mice (67).…”
Section: Discussioncontrasting
confidence: 56%
“…10,[42][43][44] Our observation also supports the need for combining different markers (ie, TREC content and Ki67 expression) for a correct thymic output evaluation in human beings, as recently suggested by different authors. 45,46 In summary, our data show that T-cell reconstitution after GT for ADA-SCID, like allogeneic BMT, is driven by de novo thymopoiesis, as well as by homeostatic expansion of naive and memory T cells, especially in the first months after treatment.…”
Section: Discussionsupporting
confidence: 88%
“…[4][5][6] In patients with ADA-SCID, transplant of retrovirally transduced CD34 1 cells after low-intensity conditioning has resulted in longterm engraftment of multilineage HSCs 7 with correction of metabolic and immunologic defects. 4,8 After BMT or in lymphopenic conditions (ie, resulting from genetic or acquired immunodeficiencies or infections), the T-cell compartment can be sustained by (1) homeostatic proliferation of pre-existing T-cell clones, [9][10][11] (2) de novo thymopoiesis, or (3) extrathymic differentiation. 12 After BMT, the reconstitution of the peripheral T cells is mainly driven by memory cells, particularly at early follow-up, in both pediatric and adult recipients.…”
mentioning
confidence: 99%
“…During HIV-1 infection, the production of IL-7 is amplified to maintain homeostasis in response to T cell depletion (Napolitano et al 2001). The exogenous administration of IL-7 enhances the regeneration of the T cells after transplantation of bone marrow, and its positive effect on immune reconstitution is associated with a considerable increase in thymopoiesis (Mackall et al 2001). Notably, application of IL-7 has been reported to enhance immune reconstitution during lymphopenia.…”
Section: Can Ati Be Reversed Therapeutically?mentioning
confidence: 99%